Contingency and Causality - Adam Wickberg (Media Theory, 2020)
This article analyses specific acts of handwriting on paper in relation to digitization. It frames the artifact of the digital image of the handwritten note as a post-digital object, which is defined by the inseparability of analogue and digital and also highlights a relation to the digital in which internal opposition is a part of it. The article discusses the media function of post-digital contingency through two particular cases of handwriting on paper that circulates online. Firstly, it analyses post-digital handwriting in the political sphere using the example of the social media posting and sharing of Donald Trump’s signature after he took presidential office. Secondly, it elaborates post-digital handwriting as an aesthetic phenomenon by discussing the Instagram account of renowned Swiss curator Hans Ulrich Obrist who has posted nearly 4,500 handwritten notes to 320,000 followers over eight years. Finally, it places these discussions into the context of the philosophy of Martin Heidegger to arrive at a better understanding of how the ontological difference of post-digital handwriting is produced.